1996
DOI: 10.1002/(sici)1096-9861(19960429)368:2<229::aid-cne5>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of ORL‐1 in the central nervous system of the rat

Abstract: A novel member of the opioid receptor family (ORL-1) has been cloned from a variety of vertebrates. ORL-1 does not bind any of the classical opioids, although a high affinity endogenous agonist with close homology to dynorphin has recently been identified. We have generated a monoclonal antibody to the N-terminus of ORL-1 to map areas of receptor expression in rat central nervous system (CNS). Intense and specific immunolabeling was observed in multiple areas in the diencephalon, mesencephalon, pons/medulla, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 0 publications
8
68
0
1
Order By: Relevance
“…Neuronal perikarya are shown as solid circles, and fibers-terminals as short curved lines and dots. Data from Neal et al (1999); very similar results were reported by Anton et al (1996). AA, anterior amygdala; ABL, basolateral nucleus of amygdala; AC, anterior commissure; ACB, nucleus accumbens; ACE, central nucleus of the amygdala; ACO, cortical nucleus of amygdala; AD, anterodorsal nucleus of thalamus; AL, anterior lobe of pituitary; AM, anteromedial nucleus of thalamus; AMB, nucleus ambiguus; AME, medial nucleus of the amygdala; AON, anterior olfactory nucleus; ARC, arcuate nucleus; AV, anteroventral nucleus of thalamus; BST, bed nucleus of the stria terminalis; CC, corpus callosum; CGX, cingulate cortex; CM, central-medial nucleus of thalamus; COCH, cochlear nuclear complex; CPU, caudate-putamen; CST, corticospinal tract; DH, dorsal horn of spinal cord; DG, dentate gyrus; DM, dorsomedial nucleus of hypothalamus; DNV, dorsal motor nucleus of vagus; DTN, dorsal tegmental nucleus; ENT, entorhinal cortex; FN, fastigial nucleus of cerebellum; FRX, frontal cortex; GL, glomerular layer of olfactory bulb; GP, globus pallidus; HM, medial habenular nucleus; HPC, hippocampus; IC, inferior colliculus; IL, intermediate lobe of pituitary; IP, interpeduncular nuclear complex; LC, nucleus locus coeruleus; LG, lateral geniculate nucleus; LHA, lateral hypothalamic area; LRN, lateral reticular nucleus; MF, mossy fibers of hippocampus; MFN, motor facial nucleus; MG, medial geniculate nucleus; ML, medial lemniscus; MM, medial mammillary nucleus; MNT, mesencephalic nucleus of trigeminal; MVN, medial vestibular nucleus; NCU, nucleus cuneatus; NCX, neocortex; NDB, nucleus of diagonal band; NL, neural lobe of pituitary; NRGC, nucleus reticularis gigantocellularis; NRPG, nucleus reticularis paragigantocellularis; NTS, nucleus tractus solitarius; OCX, occipital cortex; OT, optic tract; OTU, olfactory tubercle; PAG, periaqueductal gray; PAX, periamygdaloid cortex; PBN, parabrachial nucleus; PC, posterior commissure; PIR, piriform cortex; PN, pons; POA, preoptic area; PP, perforant path; PV, periventricular nucleus of thalamus; PVN(M), paraventricular nucleus (pars magnocellularis); PVN(P), paraventricular nucleus (pars parvocellularis); RD, nucleus raphe dorsalis; RE, nucleus reuniens of thalamus; RF, reticular formation; RM, nucleus raphe magnus; RME, nucleus raphe medianus; SC, superior colliculus; SCP, superior cerebellar peduncle; SM, stria medullaris thalami; SNC, substantia nigra (pars compacta); SNR, substantia nigra (pars reticulata); SNT, sensory nucleus of trigeminal (main); SON, supraoptic nucleus; SPT, septal nuclei; STN, spinal nucleus of trigeminal; SUB, subiculum; VM, ventromedial nucleus of hypothalamus; VP, ventral pallidum; ZI, zona incerta.…”
Section: Figures and Tablessupporting
confidence: 85%
“…Neuronal perikarya are shown as solid circles, and fibers-terminals as short curved lines and dots. Data from Neal et al (1999); very similar results were reported by Anton et al (1996). AA, anterior amygdala; ABL, basolateral nucleus of amygdala; AC, anterior commissure; ACB, nucleus accumbens; ACE, central nucleus of the amygdala; ACO, cortical nucleus of amygdala; AD, anterodorsal nucleus of thalamus; AL, anterior lobe of pituitary; AM, anteromedial nucleus of thalamus; AMB, nucleus ambiguus; AME, medial nucleus of the amygdala; AON, anterior olfactory nucleus; ARC, arcuate nucleus; AV, anteroventral nucleus of thalamus; BST, bed nucleus of the stria terminalis; CC, corpus callosum; CGX, cingulate cortex; CM, central-medial nucleus of thalamus; COCH, cochlear nuclear complex; CPU, caudate-putamen; CST, corticospinal tract; DH, dorsal horn of spinal cord; DG, dentate gyrus; DM, dorsomedial nucleus of hypothalamus; DNV, dorsal motor nucleus of vagus; DTN, dorsal tegmental nucleus; ENT, entorhinal cortex; FN, fastigial nucleus of cerebellum; FRX, frontal cortex; GL, glomerular layer of olfactory bulb; GP, globus pallidus; HM, medial habenular nucleus; HPC, hippocampus; IC, inferior colliculus; IL, intermediate lobe of pituitary; IP, interpeduncular nuclear complex; LC, nucleus locus coeruleus; LG, lateral geniculate nucleus; LHA, lateral hypothalamic area; LRN, lateral reticular nucleus; MF, mossy fibers of hippocampus; MFN, motor facial nucleus; MG, medial geniculate nucleus; ML, medial lemniscus; MM, medial mammillary nucleus; MNT, mesencephalic nucleus of trigeminal; MVN, medial vestibular nucleus; NCU, nucleus cuneatus; NCX, neocortex; NDB, nucleus of diagonal band; NL, neural lobe of pituitary; NRGC, nucleus reticularis gigantocellularis; NRPG, nucleus reticularis paragigantocellularis; NTS, nucleus tractus solitarius; OCX, occipital cortex; OT, optic tract; OTU, olfactory tubercle; PAG, periaqueductal gray; PAX, periamygdaloid cortex; PBN, parabrachial nucleus; PC, posterior commissure; PIR, piriform cortex; PN, pons; POA, preoptic area; PP, perforant path; PV, periventricular nucleus of thalamus; PVN(M), paraventricular nucleus (pars magnocellularis); PVN(P), paraventricular nucleus (pars parvocellularis); RD, nucleus raphe dorsalis; RE, nucleus reuniens of thalamus; RF, reticular formation; RM, nucleus raphe magnus; RME, nucleus raphe medianus; SC, superior colliculus; SCP, superior cerebellar peduncle; SM, stria medullaris thalami; SNC, substantia nigra (pars compacta); SNR, substantia nigra (pars reticulata); SNT, sensory nucleus of trigeminal (main); SON, supraoptic nucleus; SPT, septal nuclei; STN, spinal nucleus of trigeminal; SUB, subiculum; VM, ventromedial nucleus of hypothalamus; VP, ventral pallidum; ZI, zona incerta.…”
Section: Figures and Tablessupporting
confidence: 85%
“…Although Hcrt neurons do not constitute a nucleus, they are exclusively located in the lateral hypothalamus. In contrast, N/OFQ-containing neurons and fibers are widely distributed throughout the brain of rodents (Neal, Jr. et al, 1999;Anton et al, 1996). We observed N/OFQ-immunoreactive cells in the lateral hypothalamic area and in the area dorsal to the core of distribution of Hcrt-immunoreactive cells.…”
Section: Resultsmentioning
confidence: 99%
“…This effect of OFQ is mediated via actions at ORL-1 receptor subtype and OFQ contributes to suckling-induced prolactin release (Chesterfield et al, 2006). Since moderate to dense OFQ binding, receptor mRNA expression (Neal et al, 1999) and immunoreactivity (Anton et al, 1996) is found in arcuate nucleus, further research is required to determine if ORL-1 expression is changed during lactation.…”
Section: Discussionmentioning
confidence: 99%